Kajian Pengaturan Rute Perjalanan Berdasarkan Generalized Cost - Herawati, Herawati; Kuswati, Atik S. (Warta Penelitian Perhubungan, 2010)
The simulation of travel management st;stem by vehicle emission consideration is using faur stepsmodeling. The congestion existed in cimahi city especially in peak periods c.aused btj the increasing thenumber of private c.ars. Based on the reasons, the study only considers private car passengers as modeof transportation that will be assigned in peak hour periods. To obtain the peak period result, the resultof traffic assignment should be multiplied btj 10.5% for collector road and 9% for arterial road. Thetechnique assignment is used user equilibrium and traffic assignment is run by using generalized cost.Generalized cost is c.alculated btj actual cost and -perceive cost (emission cost). CUBE software hasbeen employed for this research to analyze traffic performance. CUBE software applies existingcondition (base) and faur scenarios. The analysis will compare between the assignment with emissioncost and the assignment without emission cost.Cimahi CihJ is study case for transportation improvements c.ause changes in the existing trafficnetwork Therefore, The scenarios are built high side friction reduction on arterial road (scenario 1)and building ringroad (scenario 2). These changes analyzed is reduction of v/c ratio as well as lengthof congested links. The first analysis is v/c ratio reduction all of scenario which compared with basecondition. The scenario 1 result create only 9 congested links with is the v/c ratio reduction of scenariobtj assignment with emission cost is 29% and withour emission cost is 26%. and scenario 2 (26%).In additional , the second scenario result achieve the best scenario bec.ause the v/c ratio reductionwithout cost is 31 % with 6 congested links and assignment with emission cost is 26% with 2congested links The result of both scenarios shJw that assignment with consideration vehicle emissioncost more efektif because provide more v/c ratio reduction and number of congested link reductions.Key words: traffic assignment, private c.ar, peak hour, emission.